Effect of Sports Vision Training on Playing Ability of Table Tennis Players: The impact of sports vision training on the playing ability of table tennis players (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Abstract – Vision is the signal that directs the body to respond and provides athletes with the information regarding where and when to perform. The present study sees the effect of 12 (twelve) week of sports vision training programme on playing ability of table tennis players. It involves forty (N=40) male state level table tennis players from Zappers Table Tennis Academy Haldwani, Uttarakhand, age ranging between 14 to 17 years as a participant for the study. Participants were divided in two equal group 20 (control group) and 20 (training group). Control group did their regular table tennis practice and training group performs the sports vision training programme too. Pre data collected before the training for both of the groups and post data collected after 12 (twelve) week of training. Level of significance was set at .05. Results of the study showed the significant improvement in playing ability of training group in comparison of control group. Study showed the relationship between the sports vision training programme and table tennis performance.